PERAN TASK FORCE MALUKU IDN-NL DALAM MEMPERTAHANKAN NKRI - ", Satirah; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to provide an overview regarding the Task Force Maluku IDN-NL and its role in sustaining NKRI and explain about the existence of the Moluccan diaspora in the Netherlands and lays out some of the efforts made by the Task Force Maluku IDN-NL to NKRI, as well as in maintaining the connection for the Moluccan diaspora in the Netherlands.This research is qualitative research that uses descriptive methods, techniques and data collection from the book, the interview via Email, journals, official publications and websites that are relevant. This research uses the perspective of neo-realists and the theory of multi-track diplomacy by John Mc. Donald and Louise Diamond. The object of this research is the Indonesian Diaspora Network Netherland (IDN-NL), which was set aside on a Task Force of Maluku.The results showed that the Task Force Maluku IDN -NL has a significant role as the sole representative of the entire Maluku diaspora that is in the Netherlands to maintain NKRI. This is in line with the success of the cooperation in the field of environment and health SSVA as well as the presence of circular open letter provided by TF Maluku to three College will conduct cooperation to hold the seminar "Beta Maluku Mau Maju " with the RMS in the Netherlands.Key Words : IDN-NL, Moluccas Task Force, Moluccan Diaspora, Role.